PERLINDUNGAN KONSUMEN TERHADAP PENYANDANG DISABILITAS SEBAGAI PENGGUNA JASA TRANS METRO PEKANBARU DI KOTA - Roberto Fernandes; Maryati Bachtiar; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
As a business actor in public services in the field of transportation services, the Trans Metro Pekanbaru in its service has responsibility for the obligation to guarantee the rights of consumers using Trans Metro Pekanbaru. Considering Persons with Disabilities are consumers who are vulnerable groups, they should be given more protection with respect to their specificity, namely in Law of the Republic Indonesia Number 8 of 2016 Concerning Persons with Disabilities. In its implementation, Trans Metro Pekanbaru should perform their obligation in fulfilling the consumer right as stated in Law of the Republic Indonesia Number 8 of 1999 Concerning Consumer Protection. But in reality there has been a social deviation. Trans Metro Pekanbaru doesn’t provide special facilities for disabled persons as arranged. Based on Article 242 Act (1) of Law of the Republic Indonesia Number 22 of 2009 concerning Road Traffic and Transportation state that "The Government, the Regional Government, and / or Public Transport Company shall provide special treatment in the field of Road Traffic and Transportation to persons with disabilities, Children, pregnant women, and sick people. Problems and objectives which will be discussed in this research is to know how the form of consumer protection against the Disabled as a user of Trans Metro Pekanbaru Service in Pekanbaru City.The type of research can be classified in the kind of sociological. This research was conducted at Department of Transportation of Pekanbaru and Trans Metro Pekanbaru, while population and sample are all parties related to the problem studied in this research, data source used, primary data, secondary data and tertiary data, data collecting technique In this study with interviews, questionnaires and literature studies.From the results of the research can be concluded that the Department of Transportation Pekanbaru as the manager of Trans Metro Pekanbaru has not fulfill the fulfillment of consumer with disabilities rights with maximum implementation. Special facilities intended for Disabled consumers are not available within the bus stop and some facilities are available within the bus unit. With the unavailability of this facility caused the Disabled Persons felt that their rights as consumers are not fullfilled by Trans Metro Pekanbaru. Suggestion for Department of Transportation of Pekanbaru and Trans Metro Pekanbaru to improve service and supervision for consumers especially for Consumer Disabled. This is intended to facilitate the fulfillment of the rights of Persons with Disabilities.Keywords: Consumer Protection - Consumer - Persons with Disabilities -Trans Metro Pekanbaru